Perbandingan Efektifitas Relaksasi Autogenic dan Music Therapy terhadap Tingkat Nyeri setelah Insersi Vaskuler Pasien yang Menjalani Hemodialisa - Beti Haerani; Yani Sofiani; Anwar Wardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The aim of this study was to compare the effectiveness of autogenic relaxation and music therapy on the level of pain in HD patients during vascular insertion. This study used a quasy experimental study with a post test design. The results of the study, using independent t test analysis showed that there was no significant difference in pain levels after vascular insertion in HD patients who were given autogenic relaxation with HD patients who were given music therapy and HD patients who were given a combination of autogenic relaxation and music therapy (p value = 0.896 , alpha = 0.05). The average pain level in the music therapy group was (5.00), autogenic relaxation with an average pain level (5.27) and an average pain level in the combined group between autogenic relaxation and music therapy (5.06). . In conclusion, music therapy has a lower level of pain than autogenic relaxation and a combination of the two because the respondent does not require a lot of mental effort to stay focused. Keywords: Hemodialysis, Music Therapy, Autogenic Relaxation, Pain Level